2023
DOI: 10.1097/dcr.0000000000002647
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of Complicated Diverticulitis: An Imbalance of Sulfur-Metabolizing Bacteria

Abstract: BACKGROUND:The progression to acute diverticulitis from the relatively benign condition of colonic diverticulosis is not well characterized. A smaller subset may even develop complicated (perforated) diverticulitis resulting in sepsis and/or death. Characterizing the differences between recurrent, uncomplicated diverticulitis, and the more virulent, complicated diverticulitis is necessary to guide clinical decision-making. Alterations to the microbiome offer a possible explanation for local inflammation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…A 2023 study, the largest of its kind, used RNA sequencing to compare harvested diseased and nondiseased tissue from the surgical resections of 48 patients with recurrent, uncomplicated diverticulitis and 35 patients with complicated acute diverticulitis. 28 The results showed that complicated diverticulitis tissue samples had increased sulfur-reducing bacteria compared with adjacent normal-appearing tissue and tissue samples from uncomplicated diverticulitis. Another contemporary review on the microbiome and its association with diverticulitis (which did not include the aforementioned study) delineated the limitations of the current data and use of available evidence and proposed a link between fiber intake and the microbiome in the development of diverticulitis.…”
Section: Preventing Acute Diverticulitismentioning
confidence: 95%
See 1 more Smart Citation
“…A 2023 study, the largest of its kind, used RNA sequencing to compare harvested diseased and nondiseased tissue from the surgical resections of 48 patients with recurrent, uncomplicated diverticulitis and 35 patients with complicated acute diverticulitis. 28 The results showed that complicated diverticulitis tissue samples had increased sulfur-reducing bacteria compared with adjacent normal-appearing tissue and tissue samples from uncomplicated diverticulitis. Another contemporary review on the microbiome and its association with diverticulitis (which did not include the aforementioned study) delineated the limitations of the current data and use of available evidence and proposed a link between fiber intake and the microbiome in the development of diverticulitis.…”
Section: Preventing Acute Diverticulitismentioning
confidence: 95%
“…There is a burgeoning field of study examining how the microbiome shapes the development of diverticulitis and the severity of diverticular disease. A 2023 study, the largest of its kind, used RNA sequencing to compare harvested diseased and nondiseased tissue from the surgical resections of 48 patients with recurrent, uncomplicated diverticulitis and 35 patients with complicated acute diverticulitis . The results showed that complicated diverticulitis tissue samples had increased sulfur-reducing bacteria compared with adjacent normal-appearing tissue and tissue samples from uncomplicated diverticulitis.…”
Section: Preventing Acute Diverticulitismentioning
confidence: 99%
“…Over 100 original clinical and scientific research articles have been published using these specimens. These publications have been the result of work with more than 30 collaborating scientists and relate to the genetics and pathophysiology diverticulitis, 31,32 the genetic basis of IBD, 33,34 disease phenotype/ genotype correlations, [35][36][37] mucus defense, 38,39 bowel permeability and myofibroblast function in IBD, [40][41][42][43] and colorectal cancer. 44,45…”
Section: The Hmc Carlino Family Ibcrd Biobank History and Settingmentioning
confidence: 99%